Orandi flap for penile urethral stricture: Polishing the gold standard - Goel, Apul; Kumar, Manoj; Singh, Manmeet (Canadian Urological Association Journal, 2015)
Introduction: We describe the combined use of the Orandi flap and the scrotal skin advancement flap to reduce complications for pendulous urethral stricture in men >40 years old. Methods: Over the last 40 months, 10 men underwent urethroplasty for pendulous stricture by the modified Orandi urethroplasty. In this, additionally, a midline hairless scrotal skin flap of the size of the ventral skin defect on the pendulous portion was raised based on the dartos fascia. This flap was mobilized so that it reached the pendulous portion without tension and covered the penile defect. The catheter was removed after 4 weeks. Patients were followed every 3 months using uroflowmetry and the American Urological Association (AUA) symptom score. Results: The mean age was 55.5. Of the 10 patients, the etiology was post-catheterization in 5 and idiopathic in the remaining 5. Three men also had stricture extending into the bulbous urethra (repaired using buccal graft). The mean additional time needed for the flap coverage was 36.2 minutes (range: 30–45). The median follow-up was 12 months (range: 3–40). The mean postoperative symptom score was 5.2 and the mean flow rate was 20.1 mL/sec. In 2 men, the meatus got retracted to the distal penile part (probably due to downward traction by scrotal skin). No patient complained of disfigurement. Two men reported recurrence (1 each in bulbous and penile urethra). The limitations are small number of patients and the observational nature of this study. Conclusions: The intermediate-term results show that the modified Orandi urethroplasty is an acceptable treatment option with acceptable cosmetic results.